The Influence of Promotions and Discounts on Purchase Interest of Wardah Products Among Generation Z in Makassar City - Putri Anggraeni Fajrian Safar; Sitti Hajerah Hasyim; Dedi Harianto (International Journal of Science and Environment (IJSE), 2026)
This research is motivated by the rapid development of the cosmetics industry in Indonesia, characterized by an increasing number of companies and high competition between brands, thus requiring companies to implement effective marketing strategies. Generation Z as a potential market segment has dynamic characteristics and is sensitive to promotions and prices, so their purchasing interest is important to study. This study aims to analyze the effect of promotions and discounts on purchasing interest in Wardah products among Generation Z in Makassar City. The research method used is a quantitative approach with a purposive sampling technique. Data were collected through a Likert-scale-based questionnaire distributed to Generation Z respondents in Makassar City. Data analysis was carried out using multiple linear regression, t-test, F-test, and coefficient of determination to test the research hypothesis. The results showed that promotions and discounts simultaneously have a positive and significant effect on purchasing interest with a significance value of 0.000 and a contribution of 57.7%. Partially, promotions and discounts each also have a positive and significant effect on purchasing interest, with discounts having a greater influence than promotions. The discount variable is proven to be a dominant factor in influencing Generation Z's purchasing interest in Wardah products. The conclusion of this study is that promotional and discount strategies are important factors in increasing purchasing interest, with discounts being the strongest factor in attracting consumer attention. This study is expected to be a reference for companies in designing effective marketing strategies, especially in the cosmetics industry.